Family violence : my parents hurt each other! - Havelin, Kate, 1961- (Mankato, Minnesota : LifeMatters, 2000)
Describes spousal and child abuse with emphasis on its possible causes and what people have done and can do to stop it
Includes bibliographical references and index
Keywords: Family violence -- Juvenile literature; Child abuse -- Juvenile literature; Family violence; Child Abuse